Housewives Behavior in Effort to Overcome Dengue Fever - Marylin Susanti Junias; Yuliana Radja Riwu (Journal of Health and Behavioral Science, 2020)
Dengue Hemorrhagic Fever is still a health problem. NTT is one of the provinces with the third highest number of DHF cases in Indonesia in 2019. Oesapa Village is the highest DHF distribution area in Kupang City, where there were 52 DHF cases in early 2019. The transmission of DHF cannot be separated from the presence of Aedes sp mosquitoes as vectors. The initial survey showed that all household in Oesapa sub-district still had a standard free larvae rate (<95%). The Ministry of Health launched the One Home One Jumantik movement to support the PSN 4M Plus acculturation program, which required the active role of the family, especially a housewife as an independent larva monitor. The general objective of this research is to find out the behavior of housewives as larva monitors at household. The research design used was Cross Sectional Study. Data were analyzed descriptively and presented in the form of narration, tables and figures. The results showed that housewives' knowledge in the prevention and control of dengue vector was classified as good category. Most housewives have a positive attitude in the prevention and control of dengue vector. Also the behavior of housewives in the efforts to prevent and control DHF vectors have been classified as good categories. The community is expected to continue to actively participate and continue to make efforts to control the vector of DHF by involving housewives as agents of change.